Recent Advances Toward the Discovery of Drug-Like Peptides De novo - Goldflam, Michael; Ullman, Christopher G. (Frontiers in Chemistry, 2015)
Peptides are important natural molecules that possess functions as diverse as antibiotics, toxins, venoms and hormones, for example. However, whilst these peptides have useful properties, there are many targets and pathways that are not addressed through the activities of natural peptidic compounds. In these circumstances, directed evolution techniques, such as phage display, have been developed to sample the diverse chemical and structural repertoire of small peptides for useful means. In this review, we consider recent concepts that relate peptide structure to drug-like attributes and how these are incorporated within display technologies to deliver peptides de novo with valuable pharmaceutical properties.